213k views
4 votes
Use the following graph of the function f(x) = 2x4 + 3x2 − x + 1 to answer this question: What is the average rate of change from x = 0 to x = 1?

A 0
B 1
C 4
D 5

User Knl
by
4.9k points

2 Answers

4 votes
I say it's b 1. ... ......
Use the following graph of the function f(x) = 2x4 + 3x2 − x + 1 to answer this question-example-1
User Kamyar Mirzavaziri
by
4.9k points
1 vote

Answer:

C. 4

Explanation:

Replace both values of x into the function to find their corresponding y-values.


f(0)=2(0)^(4)+3(0)^(2) -(0)+1\\f(0)=1\\\\f(1)=2(1)^(4)+3(1)^(2) -(1)+1\\f(1)=2+3-1+1\\f(1)=5

The rate of change is the slope of the function:


m=(y_(1)-y_(2))/(x_(1)-x_(2)) \\m=(1-5)/(0-1)\\m=(-4)/(-1) \\m=4

User Felene
by
4.6k points